Fine Arts: 2. The Creation of Forms: A Teaching Method to Enhance Art Creativity Among Students in Tertiary Institutions - Bardi Augustine Okola (Sciendo, 2018)
The existence of creation as narrated in the biblical stories has shown that there is advancement in humanity and in many other fields of endeavour. The creativity in art has advanced the economy, social-political and technological development of not only Europe centuries ago, but also in Africa. This advancement was much earlier realized and as a result of centers of creativity which were established to better the lives in their society. With the advancement of time, art decoration which has not been giving position because of arts aesthetical contents, began to generate success not only in the West where it originated from, but also in other continents of the world. The artist including the author and art aesthetics in Nigeria has not only been encouraged this upliftment, but, has gained enough ground to be appreciated. Decoratives are created by the artists; the use of forms embellished with colours has equally been appreciated in Nigeria and the societies of the world. The usefulness of decoration has been extended for both interior and exterior decorations for beautification and for other forms to solve other human endeavours.